Utrata wartości niefinansowych aktywów trwałych - wybrane problemy - Michalak, Marcin (Non-Financial Fixed Asset Impairment - Selected Issues, 2005)
The aim of this paper is to analyze the rules of Polish Accounting Act in the field of HOD- I financial fixed assets impairment in comparison with IAS 36 and SFAS 144. The Author concentrates I on the fundamental issues concerning recognition and measurement of non-financial fixed assets I impairment, e.g. the essence and causes of assets impairment, principles of asset impairment measuring, recoverable amount estimation principles. The analyses form a base for interpretations of Polish Accounting Law in the discussed area. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 184-196